Gestión de ventas en la comercializadora Godoy Ruiz S.A. - Flores Vite, Freddy Javier (2020)
Sales management in companies is important as it allows the efforts of employees to be oriented towards achieving business objectives, the research is aimed at detecting the problems that arise in Comercializadora Godoy Ruiz SA, for which reason a methodology was used of qualitative research with which it was possible to observe the factors that affect the company. Among the conclusions, it can be seen that training, sales standards, planning, motivation, and customer service are among the main factors detailed in the development of the case. The surveys that were applied allowed to have support for the conclusions that were reached in the study.